Toledo Adolescent Relationships Study (TARS): Wave 6, 2018-2020 - Giordano, Peggy C. ([Verlag nicht ermittelbar], 2024)
Prior research on parental incarceration has documented negative effects on various forms of child well-being ranging from conduct problems to academic deficits and eventually, an intergenerational cycle of criminal justice involvement. Yet as the National Academy of Sciences committee report on incarceration recently concluded, existing research has not adequately assessed the range of other family circumstances and disadvantages that may co-vary with the parent's criminal justice system involvement, and knowledge about basic mechanisms underlying incarceration effects remains markedly incomplete. This study builds on, a ten-year mixed method longitudinal study, the Toledo Adolescent Relationships Study (TARS), that has focused on the lives of a sample of men and women interviewed first as adolescents and four additional times across the transition to adulthood. The TARS study contains data involving patterns and seriousness of parental offending over the complete study period, as well as about other time-varying factors hypothesized to mediate incarceration-child well-being associations. The primary goal of this study is to collect survey data to examine the effect of parental incarceration on a range of child well-being outcomes, including conduct problems, academic readiness/achievement and emotional and physical health, among children born to participants in the TARS study. Child well-being outcomes includes internalizing and externalizing problems, academic readiness/attainment, and emotional and physical health. This study also includes parental disadvantages across the three subgroups of system contact, including variation in objective and subjective indicators of economic marginality, relationship difficulties, perceived stress, depression, and lack of social support.